Wildfire-Induced Changes in Flood Risk in Recreational Canyoning Areas: Lessons from the 2017 Jerte Canyons Disaster - Ortega-Becerril, José A.; Garrote, Julio; Vicente, Álvaro; Marqués, María José (Water (Basel), 2022)
Few studies identify potential hazards affecting canyoning. This activity has an increasing number of practitioners, and hence, a greater number of people are affected by potential natural hazards. Mountain rivers are located in places subject to several hydrological hazards; the risks are mostly connected with floods produced by intense storms or dam operation, but changes in hydrological factors may alter the usual basin behavior given even moderate or less severe storms. Data about flood events and the peak discharge of the 2017 flood in the two studied canyons were collected by means of a quick field survey of water levels after the flood, hydrological modeling, and soil analysis. The present research shows the dramatic consequences of a two-year return period storm affecting a guided group of canyoneers. A previous wildfire changed the soil, leading to hydrophobic conditions and increasing the flood effects. Peak discharge increased from 2 m3 s−1 in normal conditions to 12 m3 s−1 under a hydrophobic regime related to wildfire occurrence; moreover, a reduction in the time of concentration also occurred, pointing to a more powerful and dangerous flood event. In this paper, some hydrological recommendations are highlighted that will be helpful in recreational canyoning management, leading to safer practice.